PENGARUH IKLIM DI PROVINSI BENGKULU(KEUNIKAN DAN DAMPAKNYA) - Meilisa Sitompul, Laura; Wira Citra, Fevi; Silaban, Nurmintan; Citra, Fevi Wira (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2023)
Climate change is a global climate phenomenon that is triggered by global warming due to an increase in the concentration of greenhouse gases in the atmosphere. Understanding the impact of climate change on various economic sectors in Indonesia, the Indonesian government has responded through various policies outlined in laws and government regulations. Challenges in implementing climate change adaptation are also discussed based on literature studies and interpretation of documents related to climate change adaptation. Discussions were also held regarding the availability and access to climate information which is very necessary in assessing the impacts of climate change as a first step in preparing adaptation measures. The results of the study show that the availability and ease of access to data from climate observations (observations) is still homework that needs attention. The active role of the community in observing and collecting climate information is very necessary considering the limited availability of climate information. Cooperation between the Central and regional governments as well as public participation in adaptation programs are also recommended and very necessary. The community needs to be involved when preparing adaptation programs.